
How do you factor x^2 - x - 6? - x - 6? | Socratic
2016年6月4日 · Find factors of -6, then add them up individually to find the ones that add to -1 and you'll get to (x-3)(x+2) Let's start with the original: x^2-x-6 The way to factor something is to 2 numbers that will add up to -1 but multiply to -6.
How do you factor and solve x^2+x-6=0? - Socratic
2016年8月1日 · x=2 and x=-3 In a quadratic equation ax^2+bx+c=0, to solve one splits the middle term in two parts so that their sum is b and product is ac. Hence, in x^2+x-6=0 one needs to split 1xx(-6)=-6 in two parts whose sum is 1. It is apparent that these are 3 and -2, hence x^2+x-6=0 can be written as x^2+3x-2x-6=0 or x(x+3)-2(x+3)=0 or (x-2)(x+3)=0 i.e. either x-2=0 i.e. x=2 or …
How do you factor the expression x^2 - x - 6? - Socratic
2015年12月3日 · x^2 - x - 6 = (x - 3)(x + 2) There are many possible ways to gain the factorisation. Let me show you one of them.
How do you solve x^2+5x+6>0? - Socratic
2018年3月22日 · Given: We are given the inequality:. #color(red)(x^2+5x+6>0# #color(purple)("Step 1")# Write this inequality as #color(green)(x^2+5x+6=0# to factorize.
How do you solve x^2 - 6x + 6 = 0? - Socratic
2015年8月2日 · When do you have "no solution" when solving quadratic equations using the quadratic formula
X+9/x=6,then x2+9/x2=? - Socratic
2018年5月20日 · What are the units used for the ideal gas law?
How do you solve the inequality -x^2 - x + 6 <0? - Socratic
2018年5月12日 · x< -3" or "x>2 >"factor the quadratic" -(x^2+x-6)<0 rArr-(x+3)(x-2)<0 "find the zeros by solving" (x+3)(x-2)=0 rArrx=-3" or "x=2 "since the coefficient of "x^2" term ...
How do you solve the inequality: x^2 + x - 6 < 0? - Socratic
2015年8月22日 · Solve f(x) = x^2 + x - 6 < 0 Ans: Open interval (-3, 2) First, find the two real roots (2 x-intercepts) by solving f(x) = 0 Factor pairs of (-6) --> (-2, 3). This sum is 1 = b. Then, the 2 real roots are: 2 and -3. Use the algebraic method to solve f(x) < 0. Inside the interval (-3, 2), f(x) is negative (f(x) < 0), having the opposite sign to a = 1. Answer by open interval (-3, 2).
How do you solve x^2-6=0? - Socratic
2016年8月14日 · x=+-sqrt6 x^2-6=0 x^2=6 x=+-sqrt6. Algebra Quadratic Equations and Functions Use Square Roots to Solve Quadratic Equations
How do you solve x² + x = 6? - Socratic
2016年3月24日 · x=-3, 2 x^2+x=6 => Subtract 6 from both sides: x^2+x-6=0 => x=3x-2x: x^2+3x-2x-6=0 => factor by grouping: x(x+3)-2(x+3)=0 (x+3)(x-2)=0 The Zero Product Property: if ab=0, then either a=0 or b=0, or both. x+3=0 => x=-3 x-2=0 => x=2